2019
DOI: 10.1111/jace.16297
|View full text |Cite
|
Sign up to set email alerts
|

Heteroepitaxial growth of thick 3C‐SiC (110) films by Laser CVD

Abstract: Previously, we found 3C-SiC films favor to grow in <111> orientation on Si (110) (https://doi.org/10.1111/jace.15260). However, epitaxial growth of thick <110>-3C-SiC is still a big challenge. In this study, thick 3C-SiC (110) epitaxial films were prepared on Si (110) substrate by laser chemical vapor deposition (LCVD) using hexamethyldisilane (HMDS) in H 2 atmosphere. The investigation of growth mechanism showed that the laser of LCVD played an important role during the depositions. Observation by high-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…For kinetic considerations, the activation energies ( E a ) of the specimens calculated from Figure 4 by using the Arrhenius equation, [ 42 ] as about only 1.90–25.84 kJ mol −1 in the range of 973–1273 K, which were much lower than that in CRR domain. [ 43 ] Thus, the LCVD processes fell within the MTR domain, while the processes might fall in the CCR domain in most traditional methods. In the range of 973–1273 K, a high laser power density of up to 3.5–4.4 × 10 6 W m −2 was more efficient for LCVD growth of β‐Ga 2 O 3 than conventional methods.…”
Section: Resultsmentioning
confidence: 99%
“…For kinetic considerations, the activation energies ( E a ) of the specimens calculated from Figure 4 by using the Arrhenius equation, [ 42 ] as about only 1.90–25.84 kJ mol −1 in the range of 973–1273 K, which were much lower than that in CRR domain. [ 43 ] Thus, the LCVD processes fell within the MTR domain, while the processes might fall in the CCR domain in most traditional methods. In the range of 973–1273 K, a high laser power density of up to 3.5–4.4 × 10 6 W m −2 was more efficient for LCVD growth of β‐Ga 2 O 3 than conventional methods.…”
Section: Resultsmentioning
confidence: 99%
“…• Q. Xu 49 et al and Q. Sun et al 50 also applied laser CVD to grow 〈111〉-3C-SiC using HMDS as both Si and C source. The investigators reported that the morphology of the 〈111〉-oriented 3C-SiC films evolved from mosaic to whisker to cauliflower-like shapes as HMDS flow rate increased.…”
Section: Cubic 3c-sic: As Discussed Above Extensive Research Has Beenmentioning
confidence: 99%
“…Most CVD-produced polycrystalline 3C-SiC have selective orientation, and different selective orientations have a substantial effect on the characteristics of SiC. 22,23 There are two types of calculations for the type of orientation; the TC (hkl) weave factor calculation, which visualizes the degree of orientation of crystals with multiple orientations, and the Lotgering orientation factor calculation, which better characterizes the individual orientation variations. For 3C-SiC, only h111i and h110i are common orientations.…”
Section: Table 1 Deposition Conditions Of Each Samplementioning
confidence: 99%